2004
DOI: 10.1029/2003ja010333
|View full text |Cite
|
Sign up to set email alerts
|

Two types of energy‐dispersed ion structures at the plasma sheet boundary

Abstract: [1] We study two main types of ion energy dispersions observed in the energy range $1 to 14 keV on board the Interball-Auroral (IA) satellite at altitudes 2-3 R E at the poleward boundary of the plasma sheet. The first type of structure is named velocity dispersed ion structures (VDIS). It is known that VDIS represent a global proton structure with a latitudinal width of $0.7-2.5°, where the ion overall energy increases with latitude. IA data allow to show that VDIS are made of substructures lasting for $1-3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 57 publications
4
74
0
1
Order By: Relevance
“…These Polar results were later confirmed with ion statistical data from the polar orbiting Interball-Auroral satellite by Sauvaud and Kovrazhkin (2004), data taken at altitudes of 2 to 3 R E , and with some event data (at R>4 R E ) from the Cluster satellites as well (Sauvaud and Kovrazhkin, 2004;Keiling et al, 2004). The Sauvaud and Kovrazhkin study treats the stepping up kind of events as a separate type (VDIS), based in part on their occurring during reduced magnetic activity and in association with less energetic electrons.…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations
“…These Polar results were later confirmed with ion statistical data from the polar orbiting Interball-Auroral satellite by Sauvaud and Kovrazhkin (2004), data taken at altitudes of 2 to 3 R E , and with some event data (at R>4 R E ) from the Cluster satellites as well (Sauvaud and Kovrazhkin, 2004;Keiling et al, 2004). The Sauvaud and Kovrazhkin study treats the stepping up kind of events as a separate type (VDIS), based in part on their occurring during reduced magnetic activity and in association with less energetic electrons.…”
Section: Introductionsupporting
confidence: 64%
“…The source can be expected to be as close as the ∼19 R E Cluster apogees at times, or closer still (e.g. Lennartsson et al, 2001;Sauvaud and Kovrazhkin, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible and even likely that different types of ion beams are generated by different mechanisms under different conditions. For example, it was found that the active and quiet magnetotail can lead to ion beams with different properties giving justification for the existence of several energization mechanisms (Sauvaud and Kovrazhkin, 2004). In spite of ample observations, little has been conclusively confirmed about the impact of PSBL ion beams on auroral and magnetotail dynamics.…”
Section: Introductionmentioning
confidence: 99%